Characterization of the region encoding the CO-induced hydrogenase of Rhodospirillum rubrum. - Fox, J D (1996)
In the photosynthetic bacterium Rhodospirillum rubrum, the presence of carbon monoxide (CO) induces expression of several proteins. These include carbon monoxide dehydrogenase (CODH) and a CO-tolerant hydrogenase. Together these enzymes catalyze the following conversion: CO + H2O --> CO2 + H2. This system enables R. rubrum to grow in the dark on CO as the sole energy source. Expression of this system has been shown previously to be regulated at the transcriptional level by CO. We have now identified the remainder of the CO-regulated genes encoded in a contiguous region of the R. rubrum genome. These genes, cooMKLXU, apparently encode proteins related to the function of the CO-induced hydrogenase. As seen before with the gene for the large subunit of the CO-induced hydrogenase (cooH), most of the proteins predicted by these additional genes show significant sequence similarity to subunits of Escherichia coli hydrogenase 3. In addition, all of the newly identified coo gene products show similarity to subunits of NADH-quinone oxidoreductase (energy-conserving NADH dehydrogenase I) from various eukaryotic and prokaryotic organisms. We have found that dicyclohexylcarbodiimide, an inhibitor of mitochondrial NADH dehydrogenase I (also called complex I), inhibits the CO-induced hydrogenase as well. We also show that expression of the cooMKLXUH operon is regulated by CO and the transcriptional activator CooA in a manner similar to that of the cooFSCTJ operon that encodes the subunits of CODH and related proteins.